Designing an EU Ship Recycling Licence: A Roadmap. (July 2020) - Devaux, Caroline; Nicolaï, Jean-Philippe
Abstract: Faced with the widespread use of dismantling sites in Asia, whose processes present alarming health and environmental issues, the European Commission has raised the question of implementing a financial mechanism to encourage shipowners to use higher standards for ship recycling. This mechanism would take the form of a recycling licence applicable to any ship wanting to call at a port within EU territory, whether flying the flag of an EU Member State or of a third country. The present paper aims to critically assess the main features of the EU's proposed mechanism from a legal and economic perspective and to examine the criticisms the mechanism has received to date. Our study shows that reform is desirable but that the nature and success of the proposed licence remain uncertain, depending on whether the mechanism is able to provide sufficient incentives. In this light, the paper makes several suggestions designed to improve the project's economic and legal viability. It also shows that such a project could speed up the entry into force of the Hong Kong Convention for the Safe and Environmentally Sound Recycling of Ships adopted in May 2009, whose ratification process has been severely delayed.